Development of a user-friendly, low-cost home energy monitoring and recording system. (15th September 2016) - Fletcher, James; Malalasekera, Weeratunge
Abstract: This paper reports research undertaken to develop a user-friendly home energy monitoring system which is capable of collecting, processing and displaying detailed usage data. The system allows users to monitor power usage and switch their electronic appliances remotely, using any web enabled device, including computers, phones and tablets. The system aims to raise awareness of consumer energy use by gathering data about usage habits, and displaying this information to support consumers when selecting energy tariffs or new appliances. To achieve these aims, bespoke electrical hardware, or ' nodes ', have been designed and built to monitor power usage, switch devices on and off, and communicate via a Wi-Fi connection, with bespoke software, the ' server '. The server hosts a webpage which allows users to see a real-time overview of how power is being used in the home as well as allowing scheduled tasks and triggered tasks (which respond to events) to be programmed. The system takes advantage of well standardised networking specifications, such as Wi-Fi and TCP, allowing access from within the home, or remotely through the internet. The server runs under Debian Linux on a Raspberry Pi computer and is written in Python, HTML and JavaScript. The server includes advanced functionality, such as device recognition which allows users to individually monitor several devices that share a single node . The openPicus Flyport is used to provide Wi-Fi connectivity and programmable logic control to nodes . The Flyport is programmed with code compiled from C. Highlights: The system is capable of collecting, processing and displaying detailed usage data. The system is built using commonly available components and software. Nodes in this system can communicate via a Wi-Fi connection with a server. The data saved in the server can be used in smart grid applications.